Using KNN algorithm for classification of textual documents - Moldagulova A.; Sulaiman R.B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Classification (of information); Information retrieval systems; Learning systems; Nearest neighbor search; Tellurium compounds; Text processing; Automated classification; Exponential growth; K nearest neighbor (KNN); k-NN algorithm; Text classification; Textual documents; Two sources; Learning algorithms